Risk Perception sebagai Variabel Mediasi: Overconfidence Bias dan Availability Bias terhadap Keputusan Investasi - Hanny Novita Khairunnisa; Tiar Lina Situngkir; Arif Fadilla (Jurnal Kajian dan Penelitian Umum, 2026)
This study aims to examine the extent to which overconfidence bias and availability bias influence investment decisions, with risk perception serving as an intervening variable, particularly among retail investors in the Greater Jakarta area. A quantitative approach using SEM-PLS analysis was selected as the methodological framework for this study. The findings reveal that both behavioral biases—namely, overconfidence bias and availability bias—have a proven influence on investors’ risk perception. However, there is a significant difference in terms of direct influence on investment decisions: overconfidence bias does not show a significant direct impact, while availability bias and risk perception are proven to significantly influence investment decision-making. This study also confirms the mediating role of risk perception in two distinct patterns. In relation to overconfidence bias, risk perception acts as a full mediator, meaning that the effect of overconfidence bias on investment decisions can only be mediated through risk perception. Meanwhile, in relation to availability bias, risk perception functions only as a partial mediator, meaning that availability bias still has a direct influence on investment decisions outside the mediation pathway. Overall, the results of this study reinforce the idea that risk perception plays a crucial role in shaping and determining the direction of investment decisions.